Vedolizumab blocks alpha 4 beta 7 integrin-mediated T cell adhesion to MAdCAM-1 in microscopic colitis - Besendorf, Laura; Müller, Tanja; Geppert, Carol-Immanuel; Schneider, Ines; Mühl, Laura; Atreya, Imke; Vitali, Francesco; Atreya, Raja; Neurath, Markus; Zundler, Sebastian (Therapeutic Advances in Gastroenterology, 2022)
Background: In Crohn's disease and ulcerative colitis, the anti-alpha 4 beta 7 integrin antibody vedolizumab has demonstrated efficacy in phase III trials and has been successfully used under real-world conditions. Occasionally, it has also been used in other forms of inflammatory bowel disease (IBD) such as microscopic colitis (MC). However, the mechanisms of vedolizumab in MC have not been studied to date. Therefore, we aimed to investigate the expression and functional role of gut-homing integrins and in particular alpha 4 beta 7 integrin in a cohort study in MC.
CRIS-Team WoS Importer:2022-07-08
Keywords: α4β7 integrin; microscopic colitis; T cell trafficking; vedolizumab

α4β7 integrin-dependent adhesion of T cells to MAdCAM-1 is blocked by vedolizumab in patients with chronic refractory pouchitis - Melde, Michaela; Müller, Tanja; Schneider, Ignaz Hans Friedrich; Geppert, Carol-Immanuel; Mühl, Laura; Besendorf, Laura; Allner, Clarissa; Becker, Emily; Atreya, Imke; Vitali, Francesco; Atreya, Raja; Neurath, Markus; et al. (Therapeutic Advances in Gastroenterology, 2021)
Background: The anti-α4β7 integrin antibody vedolizumab is an established therapeutic option for the treatment of inflammatory bowel disease (IBD). It has also been successfully used in patients with chronic antibiotic-refractory pouchitis following proctocolectomey with ileal pouch-anal anastomosis. However, the expression and function of gut-homing markers as well as strategies to predict the response to vedolizumab in pouchitis are understudied so far. Methods: We used flow cytometry and dynamic adhesion assays to study the expression and function of gut-homing integrins on T cells from patients with pouchitis and controls as well as longitudinally during therapy of pouchitis with vedolizumab. Moreover, we describe clinical effects of vedolizumab in a cohort of patients with pouchitis. Results: T cells from patients with pouchitis express a specific profile of gut-homing integrins. Integrin α4β7 on T cells from patients with pouchitis mediates adhesion to mucosal addressin cell adhesion molecule (MAdCAM)-1, which can be blocked by vedolizumab in vitro. Vedolizumab efficiently treats pouchitis in a portion of patients and response correlates with dynamic adhesion profiles to MAdCAM-1. Conclusion: Our data suggest that T cell trafficking seems to be important for the pathogenesis of pouchitis and support the therapeutic use of vedolizumab. Integrin function might serve as a biomarker to predict response to vedolizumab.
CRIS-Team Scopus Importer:2021-12-17
Keywords: ileal pouch-anal anastomosis; pouchitis; proctocolectomy; T cells trafficking; vedolizumab